Postpartum IUD insertion in Peru: Experience in nine hospitals - Guzmán, Alfredo (2015)
This paper presents different strategies available for the delivery of family planning services, and describes in detail post partum contraception with emphasis in the intrauterine device (IUD). It presents the world and national experiences and the results of the first operative research performed in the country in nine public hospitals (5 from in the Peruvian Social Security Institute and 4 from the Ministry of Health). The study compares the results obtained in the surveys during prenatal and post partum care and the follow up carried out in an aleatory sample of patients and users. The results reveal the strategv is acceptable, safe and cost effective, and will increase prevalence of long lasting methods with low failure rates. Notwithstanding there is a highly unsatisffied demand to limit or space and births, there are myths and fears in relation with different contraceptive methods that require better information and counseling in family planning.